The effect of cyanotic and acyanotic congenital heart disease on children’s growth velocity - Dewi Awaliyah Ulfah; Endang Dewi Lestari; Harsono Salimo; Sri Lilijanti Widjaya; Bagus Artiko (Indonesian Pediatric Society, 2017)
Background Congenital heart disease (CHD) can lead to failure to thrive. Decreased energy intake, malabsorption, increased energy requirements, and decreased growth factors (growth hormone/insulin-like growth factor 1 axis) are related to malnutrition and growth retardation in children with CHD.Objective Tocompare the impact of cyanotic and acyanotic CHD on children’s growth velocity (using the 2009 WHO growth velocity chart).Methods This study was conducted in patients less than 24 months of age with CHD in the Pediatric Cardiology Specialist Unit Dr. Moewardi Hospital, Surakarta, Central Java, from December 2016 to February 2017. Subjects’ weights were evaluated at the beginning of the study and two months later. Data were compared to the WHO Growth Velocity chart and analyzed by Chi-square test.Results Of 46 patients with CHD (23 cyanotic, 23 acyanotic), 10 patients (21.7%) were identified with failure to thrive, i.e., < 5th percentile. Significantly more children with acyanotic CHD were in the >5th percentile for growth velocity than were children with cyanotic CHD (OR 5.600; 95%CI 1.038 to 30.204; P=0.032). Acute upper respiratory tract infection was not significantly associated with growth velocity (OR 2.273; 95%CI 0.545 to 9.479; P=0.253).Conclusion Children with cyanotic CHD have 5.6 times higher risk of failure to thrive than children with acyanotic CHD.